Determinants of Diabetes Mellitus Complication Prevention in Rural Communities - Hurmia Hurmia; Fahmi Ichwanyah; Radhiah Zakaria; Meutia Zahara; Maidar Maidar (GLOBAL HEALTH SCIENCE GROUP, 2026)
Diabetes mellitus is a major global public health problem that contributes significantly to morbidity, mortality, and decreased quality of life due to its long-term complications. Rural communities are particularly vulnerable to diabetes mellitus complications because of limited access to healthcare services, inadequate health education, low socioeconomic status, and insufficient preventive health behaviors. The purpose of this study is to analyze the determinants of diabetes mellitus complication prevention in rural communities. This quantitative study with a cross-sectional design in May 2025. The study population consisted of 348 respondents with a sample of 186 respondents selected using random probability sampling. Data were collected through questionnaires. The results showed that all questionnaire items were valid, with r-count values ranging from 0.412 to 0.845, exceeding the r-table value. Reliability testing was conducted using Cronbach’s Alpha, and all variables demonstrated good internal consistency, including diabetes complication prevention (0.892), knowledge (0.846), motivation (0.874), and health examination (0.831). Analyzed using logistic regression. The results showed a significant relationship between education (0.000), type of employment (0.000), income level (0.00), knowledge (0.000), attitude (0.000), self-motivation (0.000), family support (0.000), and access to health services (0.000) with efforts to prevent DM complications. In contrast, age (0.067), gender (0.291), and anxiety level (0.080) were not significantly related. The most dominant variable was self-motivation with an OR of 144.7. The conculsion is education, occupation, income, knowledge, attitude, family support, healthcare access, and especially self-motivation significantly influenced diabetes complication prevention efforts in rural communities.